2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Earned Income Tax Credit [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS, 2003)
Earned income tax credit provides qualified employees with earned income tax credits for their tax returns or advanced payments throughout the year. This is EDIS document FE394, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.